Do Software Development Projects Dispersed Across the Globe Deliver the Goods? - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2007)
Higher demands on computer systems and networks compel technology companies to assign software development duties across many dispersed centres in the US, India, China and elsewhere. In actual practice, does this distributed development model work well? Singapore Management University information systems professors Narayan Ramasubbu and Rajesh Krishna Balan examined this question in an award-winning paper, “Globally Distributed Software Development Project Performance: An Empirical Analysis,” presented recently at a joint meeting of the European Software Engineering Conference and the ACM SIGSOFT symposium.